2011
DOI: 10.1111/j.1749-6632.2010.05925.x
|View full text |Cite
|
Sign up to set email alerts
|

Urban biodiversity: patterns and mechanisms

Abstract: The patterns of biodiversity changes in cities are now fairly well established, although diversity changes in temperate cities are much better studied than cities in other climate zones. Generally, plant species richness often increases in cities due to importation of exotic species, whereas animal species richness declines. Abundances of some groups, especially birds and arthropods, often increase in urban areas despite declines in species richness. Although several models have been proposed for biodiversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
352
2
16

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 443 publications
(407 citation statements)
references
References 108 publications
12
352
2
16
Order By: Relevance
“…Chace and Walsh 2006;Clergeau et al 2006;Faeth et al 2011;Mikami and Mikami 2014;Sanz and Caula 2015), suggesting that fewer species are able to exploit increasingly urbanized habitats. For birds, several studies have also found that species richness peaks at an intermediate level of…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chace and Walsh 2006;Clergeau et al 2006;Faeth et al 2011;Mikami and Mikami 2014;Sanz and Caula 2015), suggesting that fewer species are able to exploit increasingly urbanized habitats. For birds, several studies have also found that species richness peaks at an intermediate level of…”
Section: Discussionmentioning
confidence: 99%
“…Evans et al 2010), and urban communities tend to be dominated by the same or similar species, even in widely geographically separated areas, hence it is a process that seemingly promotes biotic homogenization (McKinney 2006). As a consequence, there is a general (but by no means universal) pattern of lower animal and plant species richness with increasing urbanization (Faeth et al 2011), although those species that are able exploit urban environments may often occur at higher densities than their counterparts in (semi-)natural habitats, in particular, birds and arthropods (Faeth et al 2011). Indeed, Chace and Walsh (2006) reviewed the published literature on birds and found a general intermediate peak in species richness along the urban gradient.…”
Section: Introductionmentioning
confidence: 99%
“…This is clearly visible in review papers, where examples from smaller cities are very scarce (Niemelä and Kotze 2009;Faeth et al 2011;Aronson et al 2014;Bonthoux et al 2014). The possible reason behind favouring large cities in research is the fact that large metropolitan areas represent the peak of urbanization and therefore can be used as appropriate models to analyse the effects of habitat fragmentation in the extreme (Vignoli et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found that within cities, native flora and fauna communities are usually radically altered in terms of species composition, abundance, richness and evenness (Nilon and Pais 1997;van der Ree and McCarthy 2005;Gagné and Fahrig 2011;Faeth et al 2011;Jones and Leather 2012;Aronson et al 2014;Lattman et al 2014). In the case of urban fauna, the main effects of urbanization are: biotic homogenization -a decrease in richness and diversity of fauna species along with the degree of urbanization (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation